2022
DOI: 10.46300/9106.2022.16.20
|View full text |Cite
|
Sign up to set email alerts
|

Finely Crafted Features for Traffic Sign Recognition

Abstract: Traffic sign recognition (TSR) is the basic technology of the Advanced Driving Assistance System (ADAS) and intelligent automobile, whileas high-qualified feature vector plays a key role in TSR. Therefore, the feature extraction of TSR has become an active research in the fields of computer vision and intelligent automobiles. Although deep learning features have made a breakthrough in image classification, it is difficult to apply to TSR because of its large scale of training dataset and high space-time comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…First, they heavily rely on manually designed features that are sensitive to variations in lighting conditions, occlusions, and complex backgrounds [27]. Second, these methods often struggle to adapt to diverse traffic sign datasets and real-world scenarios, as the handcrafted features may not generalize well [28]. Despite these limitations, traditional methods served as the foundation for early traffic sign recognition research and demonstrated reasonable performance under controlled conditions [29][30][31][32].…”
Section: Traditional Traffic Sign Recognition Methodsmentioning
confidence: 99%
“…First, they heavily rely on manually designed features that are sensitive to variations in lighting conditions, occlusions, and complex backgrounds [27]. Second, these methods often struggle to adapt to diverse traffic sign datasets and real-world scenarios, as the handcrafted features may not generalize well [28]. Despite these limitations, traditional methods served as the foundation for early traffic sign recognition research and demonstrated reasonable performance under controlled conditions [29][30][31][32].…”
Section: Traditional Traffic Sign Recognition Methodsmentioning
confidence: 99%
“…The goal of the research achieved in [ 15 ] was a lightweight CNN to permit easy implementation, and the improved network LeNet-5 model was chosen for the classification of road signs. The authors in [ 16 ] raised the shortcoming of TSR methods based on using an end-to-end CNN. So, they proposed a finely crafted feature based on the color-histogram-based features and HOG features.…”
Section: Related Workmentioning
confidence: 99%
“…The method achieved an accuracy level of 93.98%. Li et al, (2022) [4] presented an approach for traffic sign recognition with finely crafted features and dimension reduction. The authors utilized the color information of traffic signs and enhanced the discrimination between images using the improved color-histogrambased feature.…”
Section: Machine Learning For Traffic Sign Recognitionmentioning
confidence: 99%